STUDY TO COMPARE THE THERAPEUTIC EFFICACY OF N-ACETYL CYSTEINE AND COMBINATION OF N-ACETYL CYSTEINE AND TAURINE IN PROTEINURIA IN DIABETIC NEPHROPATHY - Singh, Akhilesh Kumar; Agarwal, Prabhat; Kaushik, Saurabh (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objective: Proteinuria is an established risk factor for progressive damage of kidney. This proteinuria can be effectively controlled by drugs that interrupt the renin–angiotensin–aldosterone system. However, the efficacy of N-acetyl cysteine (NAC) and taurine in prevention of diabetic nephropathy (DN) is uncertain. The role of NAC and taurine in reducing of proteinuria in patients with DN was studied. Methods: The present study was undertaken in the Postgraduate Department of Medicine of S.N. Medical College, Agra. A total of 60 patients of diabetes mellitus with evidence of nephropathy were included in the study. Twenty patients were given placebo medication (Group P), 20 patients received NAC (Group A), and remaining 20 received a combination of NAC and taurine (Group B). Each group was further subdivided according to the urinary albumin excretion in 24 hrs. Subgroup 1 - Urinary albumin excretion between 30 and 300 mg/24 hrs. Subgroup 2 - Urinary albumin excretion >300 mg/24 hrs. The stastical analysis used Student's t-test. Results: On comparison, in both microalbuminuria and macroalbuminuria patients divided into three groups; the difference in magnitude of increase in proteinuria (after NAC, NAC with taurine, and placebo administration) over 24 weeks of the study period was statistically insignificant. Conclusions: In this study, there was no significant difference of proteinuria before and after NAC administration, and also in our study, there was no significant difference of proteinuria before and after taurine administration. Keywords: Albuminuria, Diabetic nephropathy, N-acetyl cysteine, Taurine.